ANALISIS EVALUASI BADAN PENYELENGGARA AD HOC PEMILIHAN UMUM 2019 DI SULAWESI TENGGARA - M Najib Husain; Muhammad Nasir; Dewi Anggraini (Universitas Halu Oleo, 2020)
This research was motivated by the illness of 436 Election organizers and the death of 6 Ad Hoc Organizers in Southeast Sulawesi. To reveal this, the study was designed which is a mix method approach. The data collection technique was carried out by distributing questionnaires to respondents with a multi-stage random sampling technique. The results showed the Ad Hoc Organizing Body at the 2019 General Elections in Southeast Sulawesi carried out all stages of the holding of the 2019 General Elections in accordance with their duties and authorities as stipulated in the regulations. The recruitment pattern of the Ad Hoc Organizing Body in Southeast Sulawesi has done openly, independently, fulfilling the physical and mental health requirements and has knowledge about electoral, so the results of the research show the Ad Hoc Organizing Agency in Southeast Sulawesi has been tasked with working independently, with integrity and professionalism. The objective condition of the workload of the Ad Hoc Administration Agency in Southeast Sulawesi, in general, the stages of election activities that are felt to be very burdensome are related to the calculation of election results and the collection of voter lists. Both of these things, the organizers need extra energy to complete the task on time and accurately. The heavy workload caused the election organizers to be sick and some died.